2004
DOI: 10.1111/j.1348-0421.2004.tb03527.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Shiga‐Toxin 1‐Resistant Stock of Vero Cells

Abstract: Shiga toxins (Stxs, also referred to as verotoxins) were first described as a novel cytotoxic activity against Vero cells. In this study, we report the characterization of an Stx1‐resistant (R‐) stock of Vero cells. (1) When the susceptibility of R‐Vero cells to Stx1 cytotoxicity was compared to that of Stx1‐sensitive (S‐) Vero cells by methylthiazolyldiphenyl‐tetrazolium bromide (MTT) assay, cell viability after 48‐hr exposure to 10 pg/ml of Stx1 was greater than 80% and less than 15%, respectively. (2) Altho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 40 publications
3
13
0
Order By: Relevance
“…The high sensitivity of Gb3-rich cells toward Stxs may be may be attributable to apoptosis, as reported by Fujii et al (20). Differences in cytotoxicity of Stx in the cloned cell lines have been described in several previous studies (21,22). Accordingly, HeLa cells were cloned in this study and the correlation between Gb3 or Gb4 content and cell viability upon exposure to Stxs was assessed.…”
Section: Discussionmentioning
confidence: 52%
“…The high sensitivity of Gb3-rich cells toward Stxs may be may be attributable to apoptosis, as reported by Fujii et al (20). Differences in cytotoxicity of Stx in the cloned cell lines have been described in several previous studies (21,22). Accordingly, HeLa cells were cloned in this study and the correlation between Gb3 or Gb4 content and cell viability upon exposure to Stxs was assessed.…”
Section: Discussionmentioning
confidence: 52%
“…TLC analysis and corresponding overlay binding assays revealed the presence of Gb3Cer, the major Stx receptor, and Gb4Cer, the less effi cient receptor, in Vero cells. Heterogeneity regarding TLC separation was observed in several previous studies and orcinol as well as Stx-detected bands of receptor GSLs suggested ceramide heterogeneity owing to fatty acids with varying acyl chain lengths ( 14,15,20,23 ). We provide here the full structural elucidation of Stx receptors of Vero-B4 cells and identifi ed Gb3Cer (d18:1, C24:0/C24:1) and Gb3Cer (d18:1, C16:0) as the prevalent Gb3Cer species (see Table 1 ), as well as similar variability for the corresponding prevalent Gb4Cer species.…”
Section: Discussionmentioning
confidence: 85%
“…Since this discovery, numerous studies have shown the functional impact of globo-series GSLs as Stx-specifi c receptors and their key role regarding toxin-mediated cytotoxicity in Vero cells ( 14,15,18,20,22,23,83 ). TLC analysis and corresponding overlay binding assays revealed the presence of Gb3Cer, the major Stx receptor, and Gb4Cer, the less effi cient receptor, in Vero cells.…”
Section: Discussionmentioning
confidence: 99%
“…Gb3Cer species with long chain fatty acids have in fact been suggested being associated with greater toxicity, because they possibly better mediate the localization of internalized toxin to the endoplasmic reticulum [61]. Although the details are unknown, the differences in the overall glycolipid composition of sensitive and resistant cells expressing compositional identical Gb3Cer species may also affect Gb3Cer recognition and the sorting route of incorporated Stx1 as shown for Vero cells [62].…”
Section: Discussionmentioning
confidence: 96%